The Aftermath of Tapering Tocilizumab After Achieving Treatment Target in Patients With Rheumatoid Arthritis: A Nationwide Cohort Study - Park, Jun Won; Kim, Min Jung; Kim, Hyoun-Ah; Kim, Jin Hyun; Lee, Eun Bong; Shin, Kichul (Frontiers in Medicine, 2022)
Background: Although recent guidelines recommend that tapering of biologic disease-modifying anti-rheumatic drugs (bDMARDs) can be considered in patients with rheumatoid arthritis (RA), there has been little evidence supporting the strategy during the non-tumor necrosis factor inhibitor treatment. This study aims to investigate the effectiveness and safety of tapering tocilizumab (TCZ) dose in patients with RA who attain low disease activity (LDA) after TCZ therapy in a nationwide cohort. Methods: Data were collected from a nationwide cohort of patients with RA receiving biologic disease-modifying anti-rheumatic drugs in South Korea (KOBIO-RA). This study included 350 patients who were treated with TCZ and achieved Clinical Disease Activity Index-low disease activity (CDAI)-LDA (CDAI ≤ 10) after 1 year of treatment. We performed longitudinal analysis considering clinical data measured at all 1-year intervals for the included patients using the generalized estimating equation. A total of 575 intervals were classified into two groups according to their dose quotient (DQ) of TCZ (tapering group vs. standard-dose group). The main outcome was maintaining CDAI-LDA in the following 1-year interval. Results: Tapering TCZ dose strategy was used in 282 (49.0%) intervals with a mean (SD) DQ of 66.0 (15.5) %. Loss of CDAI-LDA occurred in 91 (15.1%) intervals. Multivariable GEE showed that the tapering group was associated with more frequent failure to sustain CDAI-LDA (adjusted OR [95% CI]: 0.57 [0.33–0.99]), which subsequently led to impaired functional status. The likelihood of achieving DAS28-deep remission (DAS28-ESR<1.98) was also significantly lower in the tapering group (adjusted OR 0.68 [0.46–0.99]). CDAI remission was achieved in only 69 (12.0%) of the total intervals, with no significant difference in the proportion of intervals achieving the target between the two groups. Incidence of adverse events was comparable in both groups except for hypercholesterolemia, which was lower in the tapering group. Conclusions: Tapering TCZ dose after achieving LDA increases the risk of losing LDA without a significant merit in safety.